The Importance of Financial Literacy in Financial Management in Micro, Small and Medium Enterprises (MSMEs) - Dwyanti, Dwyanti (Universitas Dinamika, 2024)
This research examines the impact of financial literacy on the financial management of Micro, Small, and Medium Enterprises (MSMEs) by building upon previous studies. A robust level of financial literacy within MSMEs is crucial for enhancing the effectiveness of financial management practices. Literature review indicates that a heightened understanding of fundamental financial concepts empowers MSMEs to make informed financial decisions, contributing to their overall resilience and sustainability. A deeper comprehension of financial management aids MSMEs in identifying financial opportunities and mitigating risks when formulating long-term financial strategies. Collaborative efforts involving various stakeholders, such as government bodies, financial institutions, and non-government organizations, are essential to elevate financial literacy among MSME stakeholders. It is anticipated that this literacy enhancement will positively impact the welfare and sustainability of the MSME sector as a whole, fostering local economic growth.